Implementation of SOP for Recruitment and Selection of New Employees at PT. Antasari Semesta to Increase Company Effectiveness - Evi Silvana Muchsinati; Adeline Oktalia (Universitas Internasional Batam, 2024)
Antasari Semesta is a company engaged in expeditions that focuses on shipping goods to various destinations according to the sender's request. The company is located at the talks. Tering, Commercial Center Building, JL., Orchid Garden Complex. Based on the results of an interview with PT. Antasari Semesta, the company does not yet have SOPs to recruit the right employees. Thus, the author will design and update a new employee recruitment system that is more accurate and meets the criteria set by PT. Antasari Semesta. In carrying out this practical work, the author uses several methods, including conducting interviews, observations and documentation. The results of this recruitment and selection SOP intervention also have a positive impact on PT. Antasari Semesta shows that this recruitment and selection SOP can improve performance and develop the company through more qualified human resources.